ASUPAN VITAMIN C TERHADAP KADAR HDL PADA LANSIA DIABETES MELLITUS TIPE 2 DI PAGUYUBAN DIABETES MELLITUS SURAKARTA - Akti, Riza Rifananda; Soviana, Elida (Indonesian Journal of Nutrition Science and Food, 2022)
Abstract Type 2 diabetes mellitus is a disease with an incidence proportion of 95% of the total patients with diabetes mellitus. Type 2 diabetes mellitus is characterized by insulin resistance. Insulin resistance can lead to glucose intolerance and decreased levels of High-Density Lipoprotein (HDL). A good diet is one way to keep blood glucose under control, one of which is by consuming enough vitamin C. Vitamin C helps prevent complications of type 2 diabetes mellitus by inhibiting the production of sorbitol. Vitamin C as an antioxidant also affects the lipid profile which can increase HDL levels. This study aims to determine the relationship between vitamin C intake and HDL levels in the elderly with type 2 diabetes mellitus in the Diabetes Mellitus Society of Surakarta. This research is observational with a cross-sectional approach. Data on vitamin C intake used a semi-quantitative food frequency questionnaire (FFQ) and the results of laboratory tests for HDL levels. Data analysis using Pearson product-moment correlation test. The intake of vitamin C from foodstuffs that met the needs was 89.3%, 57.1% of the samples had low HDL levels and 42.9% had normal HDL levels. The test results of the analysis of vitamin C intake with HDL levels obtained p-value = 0.148, it can be concluded that there is no relationship between vitamin C intake and HDL levels.